PENGEMBANGAN KURIKULUM PROGRAM PAKET B - Puji Hadiyanti (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2013)
The Community Learning Center (CLC) as an educational institution to implement Package A Program is assigned to produce the graduates having equivalent competence as Junior High School does. Besides, the learners are also expected to be able to meet their needs and solve their problems. CLC has to develop the existing curriculum to complete its tasks as expected. This research is intended to know the curriculum at CLC of Tunas Bangsa, Probolinggo District, East Java, and how it develops and implements the curriculum. The research conducted as from April through July 2010, reviewed the existing curriculum using qualitative method and then developed the curriculum on the basis of local needs and potentials. The result of the study is an integrated curriculum to be used by tutors and will encourage them to improve theircompetence.